2012
DOI: 10.1111/j.1365-2362.2012.02678.x
|View full text |Cite
|
Sign up to set email alerts
|

‘Omics’‐driven discoveries in prevention and treatment of type 2 diabetes

Abstract: Glucose-based methods are currently gold standards for identifying individuals at risk of type 2 diabetes. Obviously, these methods only consider one of many pathologies of impaired glucose metabolism and they all suffer from a poor specificity as type 2 diabetes risk assessment tools. Recently, however, panels of multiple biomarkers reflecting several pre-diabetic pathologies have been developed. Their specificity and potentials for future risk stratification are discussed. As a multifactorial disorder type 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 72 publications
1
11
0
Order By: Relevance
“…Given that the current T2D susceptibility loci identified from GWAS are mostly associated with b-cell dysfunction (47,48), our findings were expected. However, the large meta-analysis GWAS focused on IR was spare, only several validated loci associated with IR have been reported.…”
Section: Discussionsupporting
confidence: 71%
“…Given that the current T2D susceptibility loci identified from GWAS are mostly associated with b-cell dysfunction (47,48), our findings were expected. However, the large meta-analysis GWAS focused on IR was spare, only several validated loci associated with IR have been reported.…”
Section: Discussionsupporting
confidence: 71%
“…At present, most holistic approaches for analysing the intestinal microbial community rely on 16S rRNA gene sequencing, a proven method to determine taxonomic composition of communities [2]. However, amplicon sequencing only provides information on who is present and not what they are doing.…”
Section: Characterization Of the Gut Microbiomementioning
confidence: 99%
“…T2D also known as hyperglycemia result from compromised insulin utilization (insulin resistance-IR) linked with insuffi cient compensatory insulin production. Long term consequence and comorbidities of T2D are nephropathy, neuropathy, retinopathy, hypertension, cardiovascular disease, dyslipidemia, cerebrovascular and peripheral vascular disease [1][2][3].…”
Section: Short Communicationmentioning
confidence: 99%
“…Since diets and genes changes one's health and susceptibility to diseases therefore, identifying T2D, as a polygenic, multifactorial disease can serve as a model for cancer, obesity, cardiovascular disease and other chronic diseases that are infl uenced by diet and environmrntal factors. Epidemiological studies showed that about 90% of T2D are as a result of fi ve major lifestyles which include diet, physical activity, smoking, obesity and alcohol consumption [1][2][3]. But among these diet is essentially given that T2D disease rooted in dysfunctional metabolism and energy fuel utilization.…”
Section: Short Communicationmentioning
confidence: 99%